Antimicrobial resistance and genomic characterization of Salmonella enterica serovar Senftenberg isolates in production animals from the United States - Srednik, Mariela E.; Morningstar-Shaw, Brenda R.; Hicks, Jessica A.; Mackie, Tonya A.; Schlater, Linda K. (Frontiers in Microbiology, 2022)
In the U.S., Salmonella enterica subspecies enterica serovar Senftenberg is among the top 5 serovars isolated from food and the top 11 serovars isolated from clinically ill animals. Human infections are associated with exposure to farm environments or contaminated food. The objective of this study was to characterize S. Senftenberg isolates recovered from diagnostic samples of production animals by analyzing phenotypic antimicrobial resistance profiles, genomic features and phylogeny. Salmonella Senftenberg isolates (n=94) from 20 U. S. states were selected from NVSL submissions (2014–2017) and tested against 14 antimicrobial drugs, and resistance phenotypes were determined. Resistance genotypes were determined using the whole genome sequencing analysis with AMRFinder and the NCBI and ResFinder databases with ABRicate. Plasmids were detected using PlasmidFinder. Integrons were detected using IntFinder and manual alignment with reference genes. Multilocus-sequence-typing (MLST) was determined using ABRicate with PubMLST database, and phylogeny was determined using vSNP. Among 94 isolates, 60.6% were resistant to at least one antimicrobial and 39.4% showed multidrug resistance. The most prevalent resistance findings were for streptomycin (44.7%), tetracycline (42.6%), ampicillin (36.2%) and sulfisoxazole (32.9%). The most commonly found antimicrobial resistance genes were aac(6ʹ)-Iaa (100%), aph(3'')-Ib and aph(6)-Id (29.8%) for aminoglycosides, followed by blaTEM-1 (26.6%) for penicillins, sul1 (25.5%) and sul2 (23.4%) for sulfonamides and tetA (23.4%) for tetracyclines. Quinolone resistant isolates presented mutations in gyrA and/or parC genes. Class 1 integrons were found in 37 isolates. Thirty-six plasmid types were identified among 77.7% of the isolates. Phylogenetic analysis identified two distinct lineages of S. Senftenberg that correlated with the MLST results. Isolates were classified into two distinct sequence types (ST): ST14 (97.9%) and ST 185 (2.1%). The diversity of this serotype suggests multiple introductions into animal populations from outside sources. This study provided antimicrobial susceptibility and genomic characteristics of S. Senftenberg clinical isolates from production animals in the U. S. during 2014 to 2017. This study will serve as a base for future studies focused on the phenotypic and molecular antimicrobial characterization of S. Senftenberg isolates in animals. Monitoring of antimicrobial resistance to detect emergence of multidrug resistant strains is critical.